The Myth Behind the Mask: Blue Crew Secret Spirit Society at The University of Toledo - Recollections of a Founder (Studying the History of Higher Education Journal, 2024)
This article traces the history of the origins and evolution of Blue Crew, a secret spirit society at The University of Toledo (UToledo), through the recollections of one of the organization’s co-founders. Secret societies have existed on U.S. college campuses since 1750; however, Blue Crew’s unique characteristics and dedication to enhancing school spirit set it apart from other institutions’ secret societies. Founded in 2000, Blue Crew consists of 10 student members whose identities are hidden behind masks, wigs, and overalls. This secret society is devoted to building community and improving the campus culture by promoting university traditions. This article provides a rare glimpse at the organization’s beginnings and its positive influence on campus. The co-founder’s firsthand account pairs with archival resources to detail the creation, development, and unique characteristics of Blue Crew, including its purpose, name origins, hidden identities, distinct uniforms, “demasking” process, and challenges experienced throughout the years. Today, Blue Crew is a thriving society with over 130 total initiated members, an alumni association, and an endowment fund that financially supports its members and activities.
Keywords: Blue Crew; secret society; spirit; school spirit; The University of Toledo; founder; secret spirit society; hidden identities; building community; positive influence; organization creation; mask; myth